2014
DOI: 10.15554/pcij.01012014.83.102
|View full text |Cite
|
Sign up to set email alerts
|

Development of a precast concrete barrier wall system for bridge decks

Abstract: The results show that the proposed precast concrete barrier system is as good as the cast-in-place concrete barrier with respect to ultimate load-carrying capacity at the deck slab-barrier connection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Patel et al 2 proposed a pre-tensioned rod connector that is inserted through the barrier and the deck. The connector is anchored to the deck by bearing plates, washers, and nuts ( Figure 1(a) ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patel et al 2 proposed a pre-tensioned rod connector that is inserted through the barrier and the deck. The connector is anchored to the deck by bearing plates, washers, and nuts ( Figure 1(a) ).…”
Section: Introductionmentioning
confidence: 99%
“…A dowel rod is connected to the steel reinforcement frame of the barrier system during prefabrication. A stainless-steel anchoring connector 2 ( Figure 3(a) ) anchors the inclined force-transmitting steel bars with stainless-steel heads under the bridge deck such that the barrier and the deck receive the load in concert. Due to the the use of stainless-steel rods, this connection doesn’t cost effective.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted on developing prefabricated barrier systems to solve the durability and construction issues associated with CIP concrete barriers. Patel et al developed a barrier-to-deck connection using post-tensioned threaded steel rods and conducted experimental studies on a series of barrier configurations representing different failure modes to investigate the behavior of the connection ( 8 ). The researchers concluded that the strength of the proposed concrete barrier wall system was comparable to the equivalent CIP concrete barrier system.…”
mentioning
confidence: 99%